The transition of Ghana’s cooling appliance sector to a circular economy via a small wins governance framework - Kuhn, S.; Opoku, R.; Diaba, D. D.; et al (Sustainable Production and Consumption, 2024)
Air conditioning poses environmental, socioeconomic, and political challenges, especially in sub-Saharan countries such as Ghana, where almost all devices are imported. Thus far, socio-economically feasible path ways for a cooling transition to a circular economy are unclear. Drawing on qualitative interviews, field ob servations and survey data, this study analyses the potential of small wins governance as a pathway to sweeping system change along Ghana’s air-conditioners’ lifecycle. The research analyses the status quo and identifies potential small wins that could lead to transformative shifts in the cooling sector. Through a mixed-methods approach encompassing interviews, surveys, and field assessments, the study uncovers small wins at four stages of the air conditioner lifecycle, from (1) import, (2) retail & purchase, (3) usage & service, and (4) end-of life management practices. For policymakers and practitioners, our results imply that they should (a) system atically encourage and reap small wins in public-private spaces in the short-term, e.g. changing the incentive structure for staff controlling imports of air conditioners, (b) adjust supporting policies as learning dynamics unfold over time (e.g., energy and refrigerant standards and labels, tax system), but (c) also keep pushing for big wins in the mid-term (e.g., constructions of a recycling plant for refrigerants in West Africa). The findings emphasize the need for a behavioural, consumer-oriented perspective for the pragmatic potential of small wins towards a circular economy. Overall, the study addresses significant gaps in the literature and suggests that bottom-up approaches may offer more success than attempting broad top-down system changes. The paper contributes to the wider discourse on social-ecological transitions and offers valuable insights for policymakers, industry stakeholders, and researchers aiming to foster sustainable practices in the cooling sector.
Research Article
Keywords: Cooling; Greenhouse gas emissions; Circular economy; Socio-technical transition